Festival Air (Songkran): Komodifikasi Budaya di Thailand - Nikodemus Niko; Atem Atem (Universitas Trunojoyo Madura, 2019)
This research aims to want to see the occurred on the discourse of cultural commodification of Songkran in Thailand. Songkran in Thailand is a religious and cultural festival, which is the celebration of New Year in Thailand. Culture of Songkran festival which then becomes bringing many foreign tourists come to some areas in Thailand like Bangkok, Chiang Mai and Phuket. This great Festival and then give effect to social, cultural as well as the economy on local community. The methods used in this study is a qualitative descriptive based on the experiences both of the author. The data analyzed i.e. secondary data that comes from a variety of scientific journals, then the primary data are analyzed based on the author’s experience when on the Songkran festival in Thailand on April, 2019. Based on the analysis that the commodification of culture happens to Songkran in Thailand is not so much to erode the authenticity of rituals. This means that the core rituals such as bathing the Buddha statues in the temples still do. Commodification is a positive impact on the local community, where on area of the festival they provided tubs for sale in range 5 THB to 15 THB. Then, foreign tourists are pouring in from various countries are also effect on the local community economy.